Caffeine lowers perceptual response and increases power output during high-intensity cycling - Doherty, M.; Smith, P.; Hughes, M.; Davison, R. (Journal of Sports Sciences, 2004)
The aim of this study was to determine the effects of caffeine ingestion on a 'preloaded' protocol that involved cycling for 2 min at a constant rate of 100% maximal power output immediately followed by a 1-min 'all-out' effort. Eleven male cyclists completed a ramp test to measure maximal power output. On two other occasions, the participants ingested caffeine (5 mg. kg(-1)) or placebo in a randomized, double-blind procedure. All tests were conducted on the participants' own bicycles using a Kingcycle trade mark test rig. Ratings of perceived exertion (RPE; 6-20 Borg scale) were lower in the caffeine trial by approximately 1 RPE point at 30, 60 and 120 s during the constant rate phase of the preloaded test (P <0.05). The mean power output during the all-out effort was increased following caffeine ingestion compared with placebo (794+/-164 vs 750+/-163 W; P = 0.05). Blood lactate concentration 4, 5 and 6 min after exercise was also significantly higher by approximately 1 mmol. l(-1) in the caffeine trial (P <0.05). These results suggest that high-intensity cycling performance can be increased following moderate caffeine ingestion and that this improvement may be related to a reduction in RPE and an elevation in blood lactate concentration.